2018
DOI: 10.5334/labphon.36
|View full text |Cite
|
Sign up to set email alerts
|

Evidence and characterization of a glide-vowel distinction in American English

Abstract: This study tests whether native speakers of American English exhibit a glide-vowel distinction ([j]- [i]) in a speech elicitation experiment. When reading sentences out loud, participants' pronunciations of 4 near-minimal pairs of pre-existing lexical items (e.g., Eston [iə] vs. pneumon [jə]) exhibit significant differences when acoustically measured, confirming the presence of a [j]- [i] distinction. This distinction is also found to be productively extended to the production of 20 near-minimal pairs of no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…It was found that intensity and F1 in the initial interval of i#V and jV# was lower than in the full high vowel in i#, indicating that the tongue body position was higher in i#V and jV# than in i#. It has been argued that semivowels have lower F1 and lower intensity than corresponding vowels (Jaggers, 2018; Maddieson & Emmorey, 1985; Myers & Hansen, 2005), so this finding is compatible with the claim in the literature that the high vocoid in i#V and jV# is a glide [j]. But it is also compatible with this vocoid being a high vowel with a higher target than the corresponding monophthong.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that intensity and F1 in the initial interval of i#V and jV# was lower than in the full high vowel in i#, indicating that the tongue body position was higher in i#V and jV# than in i#. It has been argued that semivowels have lower F1 and lower intensity than corresponding vowels (Jaggers, 2018; Maddieson & Emmorey, 1985; Myers & Hansen, 2005), so this finding is compatible with the claim in the literature that the high vocoid in i#V and jV# is a glide [j]. But it is also compatible with this vocoid being a high vowel with a higher target than the corresponding monophthong.…”
Section: Discussionmentioning
confidence: 99%
“…The greater degree of constriction results in lower intensity for the glide than for the corresponding vowel (Myers & Hansen, 2005). Differences in degree of stricture would also be reflected in F1, which is significantly lower in the glide than the corresponding high vowel in Amharic, Yoruba, and Zuni (Maddieson & Emmorey, 1985), Finnish (Myers & Hansen, 2005), and English (Jaggers, 2018). If the high vocoid in i#V and jV# is a glide, it would be expected to have lower intensity and F1 than the high vowel in i#.…”
Section: Methodsmentioning
confidence: 99%
“…To describe DAR, this study focused on formant frequency, vocalic duration, and acoustic intensity (cf. Jaggers, 2018). Vocalic context was taken into consideration to see variation in behavior.…”
Section: Methodsmentioning
confidence: 99%
“…The interaction of an introduced [DORSAL] /j/ and pre-DAR [CORONAL] /l/ could have led to assimilation based on the need to perceptually and articulatorily "recalibrate" or reanalyze (see Bybee, 2015) both approximants as they started to overlap in the inventory during the initial period of sound change. Keating (1988in Jaggers, 2018 argues that [j] is both [DORSAL] and [CORONAL], which can explain for this tendency to velarize. On another note, Browman and Goldstein (1995) argue that the tip (coronal) and back (dorsal) of the tongue are mechanically interconnected such that "in initial position, the tongue tip and the tongue dorsum gesture are roughly synchronous, whereas word-finally, the wider tongue dorsum constriction precedes the narrower tongue-tip closure" (ibid, p. 2).…”
Section: Palatalization To Velarizationmentioning
confidence: 99%